Livestock and resource management policy: Issues and priorities for research. Proceedings of the research planning workshop - Ehui, Simeon K.; Lipner, M.E. (International Livestock Centre for Africa, 1993)
This workshop was convened to help ILCA develop priorities and plan for research over the five year period, 1994-1998. The purpose of the workshop was to identify issues and priorities for research and training in the general areas of livestock and resource management policy, appropriate methodologies for research in these priorities, the role of ILCA in policy research and opportunities for collaboration with national and international institutes. The workshop addressed topics in the areas of trade and macro-economic policies, technology, policy, markets and institutions, and resource management policy.